IoT Enabled Solar Power Monitoring System - L.R. Lokesh Babu, R; Rambabu, D; Rajesh Naidu, A; D. Prasad, R; Gopi Krishna, P (International Journal of Engineering and Technology, 2018)
This paper proposes a solution and method to monitor the dust accumulated on the solar panels to get the maximum power from for effective utilization. Always the output power of the solar panel depends on the radiation reached to the solar cell. The system also displays the malfunctioned solar panels lists and whether the electrical appliance is working directly on the solar panels or the loads is on the battery. All the panels are connected, and sensors are directly connected to the central controller which monitor the panels and loads. By incorporating the IoT technology the data received from the panels and appliance are send to the cloud from through internet for the future use as well the remote user can monitor the parameters of the connected devices. The user can view the current, previous, and average parameters such as voltage, current, temperature and sun light using a graphical user interface GUI. The controller is programmed with predefined conditions with user alerts when it falls below the specified conditions. Node MCU is used as a controller.Â Â